Budidaya Ikan Lele Organik Dan Diversifikasi Produk Olahan Abon Ikan Lele - supriatna supriatna; putut wijanrko; moh mahmudi (Journal of Innovation and Applied Technology, 2018)
The purpose of this IbM activity is to disseminate the technology of organic catfish farming and organic catfish abon (shredded meat that has been boiled and fried/meat floss) in Jetak Asri Farmer Group in Mulyo Agung Village and Pesantren Darul Madhinah in Mulyorejo, Junrejo, Kota Batu. Application of organic catfish farming technology and diversification of processed products of organic catfish are expected to help increase the income of catfish farmers. The method used in this activity is to involve the community directly. Implementation of activities in the form of socialization, counseling, and training on how to cultivate organic catfish and making organic catfish abon. Organoleptic test results show that the abon made from organic catfish has the advantage of texture, taste, color that's better than the abon made from catfish are bought in the market. The obstacles faced by catfish farmers still depend on the catfish feed production plant, and the cost of feed is a very high component in the cultivation of catfish.